2021
DOI: 10.1111/iwj.13648
|View full text |Cite
|
Sign up to set email alerts
|

Pressure injury prevalence and risk factors in Chinese adult intensive care units: A multi‐centre prospective point prevalence study

Abstract: Despite increasing preventive efforts, pressure injury still occurs in intensive care patients. This study was aimed to describe pressure injury prevalence, risk factors, and prevention practices in adult intensive care patients. This was a multi‐centre, one‐day, prospective point prevalence study in which a total of 198 intensive care units from 21 provinces in China participated. Overall and ICU‐acquired prevalence in intensive care patients were 12.26% and 4.31%, respectively. Consistent with earlier report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
3
28
1
3
Order By: Relevance
“…At present, lessening pressure and maintaining a moist microenvironment for skin are the major strategies to prevent PIs/PUs in the clinical field. 10 Various dressings are applied to prevent and manage PIs/PUs for reducing tissue load and internal deformations of the supporting surface. 11,12 Polyurethane and hydrocolloid dressings are common, 13−15 but the hydrocolloid dressing is too stiff and the polyurethane dressing has poor thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, lessening pressure and maintaining a moist microenvironment for skin are the major strategies to prevent PIs/PUs in the clinical field. 10 Various dressings are applied to prevent and manage PIs/PUs for reducing tissue load and internal deformations of the supporting surface. 11,12 Polyurethane and hydrocolloid dressings are common, 13−15 but the hydrocolloid dressing is too stiff and the polyurethane dressing has poor thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the treatment, the early prophylactic intervention of PIs/PUs is the least costly and minimizes patient suffering. At present, lessening pressure and maintaining a moist microenvironment for skin are the major strategies to prevent PIs/PUs in the clinical field . Various dressings are applied to prevent and manage PIs/PUs for reducing tissue load and internal deformations of the supporting surface. , Polyurethane and hydrocolloid dressings are common, but the hydrocolloid dressing is too stiff and the polyurethane dressing has poor thermal conductivity. , The thermal conductivity and long-term stiffness of hydrogel match those of human skin, demonstrating that the hydrogel dressing has the potential for preventing PIs/PUs.…”
Section: Introductionmentioning
confidence: 99%
“…2 A systematic review and meta-analysis reported the upper and lower 95% confidence intervals (CI) of the cumulative incidence were 9.4% to 27.5% 3 in studies using skin inspection (gold standard) to identify pressure injury in the ICU. Pressure injuries occur in ICU patients due to multiple comorbidities, acute clinical conditions, and ICU treatments 4,5,6 . Pressure injury more frequently affects those with acute organ derangements such as cardiovascular instability requiring vasopressor agents and acute respiratory failure requiring invasive mechanical ventilation and sedation, analgesia, and/or neuromuscular blockade agents 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This is of concern given the burdens associated with PI for individuals [ 4 , 5 ] and healthcare facilities [ 6 ]. A secondary analysis of Labeau et al.’s [ 3 ] international point prevalence data found an ICU-acquired prevalence of 4.3% across 198 Chinese ICUs [ 7 ]. Similarly, a study across 12 Chinese hospitals reported a hospital-acquired PI prevalence of 4.5% in an ICU sample of 1,094 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%